Work-Life Balance and Occupational Stress of the Non-Gazetted Central Reserve Police Force Jawans in Chandauli - Singh, Gunjan; Srivastava, Manushi; Srivastava, Mona; Srivastava, Ratan Kumar; Srivastava, Priya (Indian Journal of Community Health, 2023)
Background: A good work life balance is essential for the employees of any organization because it emphasize on balancing the personal and professional life. However there is scarcity of studies focusing work-life balance of defense force employees in India. Aims & Objectives: The present study explores the Work-Life Balance and Occupational Stress of the Non-Gazetted Central Reserve Police Force (CRPF) Jawans. The main objective behind conducting this study is to investigate the relationship between Work Life Balance and Occupational Stress among the Non-Gazetted CRPF Jawans. Methods: The present study is a quantitative cross-sectional study based on data collected from 354 non-gazetted officers of 148th battalion in Chandauli, Uttar Pradesh, India. Data was collected from after receiving written consent from the respondents. A semi-structured questionnaire was designed to collect the data which included questions related to socio-demographic characteristics, 13 self-developed questions related to work life balance and 46 items Occupational Stress scale developed by Srivastava & Singh. Result: Most of the CRPF Jawans had moderate occupational stress and high work-life balance. The study found moderate negative correlation between Work Life Balance score and Occupational Stress score among the non-gazetted CRPF Jawans.